The Role of Interactions Between Student and Classroom Context in Developing Adaptive Self‐Efficacy in One Sixth‐Grade Mathematics Classroom. (7th May 2013) - Yetkin Özdemir, İ. Elif; Pape, Stephen J.
<x xml:space="preserve">Abstract</x> Research and theory suggest several instructional practices that could enhance student self‐efficacy. However, little is known about the ways these instructional practices interact with individual students to create opportunities or challenges for developing adaptive self‐efficacy. In this study, we focused on two sources of efficacy, mastery experiences, and social persuasion, and examined how these sources were structured for three students with different levels of mathematics achievement and self‐efficacy within a sixth‐grade mathematics classroom. Analyses within each case showed that each student experienced success and received social persuasion differently. On the other hand, analyses across the cases suggest that not only the amount but also the form (i.e., with and without assistance) of successful experiences and the type of performances (e.g., stating definitions, explaining solution procedures, sharing problem‐solving strategies, and making comments on others' ideas) through which the student experienced mastery may have played important role in developing self‐efficacy. Consistently, the amount and form of teacher feedback was different for each focal student. Examining these differences provide insight into each student's self‐efficacy assessed over the course of the study as well as the kind of support each student needed to develop adaptive self‐efficacy.